A Bottom‐up In‐situ Preparation of Graphene‐like Porous Carbon for Ultrahigh Surface Area Specific Capacitance Supercapacitors. Issue 12 (3rd November 2020) - Hao, Yisu; Liu, Zheng; Chen, Xingzhu; Liu, Jingxiao; Tang, Qunli; Hu, Aiping; Chen, Xiaohua
Abstract: Nitrogen‐doped porous carbon is an ideal electrode material for supercapacitors, and the development of efficient and inexpensive graphene‐based porous carbon is of great significance to promote its application. In this study, a bottom‐up in‐situ method is developed to grow nitrogen‐doped 3D graphene‐like porous carbon (Cu‐GL‐NPC) with Cu as a catalyst. The Cu‐GL‐NPC possessed the high nitrogen content of 7.64% and the high ratio of pyrrolic nitrogen, along with open three‐dimensional porous structure, which led to the smooth transfer of electrolyte. Consequently, the Cu‐GL‐NPC delivered an extremely high surface area specific capacitance of 49.2 μF cm −2 at a current density of 1 A g −1 . This study provides an insight for better understanding the effect of catalysts on the formation of porous carbon, which is beneficial for the design of new nanocarbon materials with different structures and different nitrogen doping types, and would offer ideas for the development of carbon materials for the next generation of supercapacitors. Abstract : Through a bottom‐up in‐situ method by using melamine‐formaldehyde resin as precursor and Cu as catalysts, a nitrogen‐doped graphene‐like porous carbon was successfully synthesized. The Cu‐GL‐NPC possessed open 3D porous structure with moderate graphitization degree, leading to ultrahigh surface area specific capacitance, which would offer ideas for the development of carbon materials for the next generation of supercapacitors.